THE RELATION OF DIET PATTERN TO DYSPEPSIA SYNDROM IN COLLEGE STUDENTS - Dwigint, Sabrine (Majority, 2015)
Abstract Dyspepsia is a group of symptoms include epigastric pain or discomfort, nausea, vomiting, bloating, early satiety, postprandial fullness, belching, regurgitating and heartburn. Dyspepsia related to the irregularity of diet pattern and interval between meals. The college students are suspectible to dyspepsia because often put off eating due to the business of doing the coursework and other activities. Keywords: activities, college students, diet pattern, dyspepsia syndrom Abstrak Dispepsia merupakan kumpulan gejala atau sindrom yang terdiri dari nyeri atau rasa tidak nyaman di epigastrium, mual, muntah, kembung, cepat kenyang, rasa perut penuh, sendawa, regurgitasi dan rasa panas yang menjalar di dada. Sindrom dispepsia berkaitan dengan ketidakteraturan pada pola makan dan jeda antara jadwal makan yang lama. Mahasiswa rentan terkena sindrom dispepsia karena sering menunda makan akibat kesibukannya dalam mengerjakan tugas kuliah dan kegiatan organisasi. Kata kunci: aktivitas, mahasiswa, pola makan, sindrom dispepsia